Exploring the chemotypic variability of Silybum marianum and Silybum eburneum by biochemical and genetic characterization - Pasquariello, Marianna; Martinelli, Tommaso; Paris, Roberta; Moschella, Anna; Colombo, Roberto; Di Bello, Alice; Frigerio, Jessica; Kheloufi, Abdenour; Mirzaabolghasemi, Mohammad Amin; Puglisi, Damiano; Esposito, Salvatore; Scalercio, Stefano; et al. (Frontiers in Plant Science, 2025)
The Silybum genus belonging to the Asteraceae family, is composed of two species, marianum and eburneum, although, in the past, their classification was not always appropriate. While Silybum marianum is very well known since ancient times for the medicinal properties of a blend of different flavonolignans contained in the achenes and named silymarin, very little information is available about Silybum eburneum chemodiversity. Here, we describe the biochemical characterization of a wide ex situ germplasm collection including 83 wild Silybum accessions collected during ad hoc sampling campaigns in Italy, Spain, Iran and Algeria as well as accessions acquired by seed GenBanks and studied at both population and single plant level. Interestingly, our results confirm the presence of only three chemotypes in S. marianum, namely A, B and C. Conversely, S. eburneum accessions, exhibit a distinct and stable chemotype (D) where isosilychristin is the predominant silymarin component. Additionally, DNA barcoding based on the ribosomal DNA region ITS2 combined with morphological phenotyping and chemotyping, successfully resolves frequently found mistakes in the identification of the two species. These findings significantly expand our knowledge of the global biodiversity of the Silybum genus and provide valuable insights for future breeding programs and potential applications in nutrition and human health sciences.